2022
DOI: 10.2478/jped-2022-0006
|View full text |Cite
|
Sign up to set email alerts
|

Potential for preventing the risk of social exclusion of children in Early Childhood Education and Care in Croatia

Abstract: This study assumes that preventing the risk of social exclusion (RSE) of children, in the context of ECEC, entails guaranteeing ECEC availability and pedagogical practices that provide children with the necessary skills for healthy and successful development. This can be achieved by strengthening the protective factors in the child’s surroundings. The overall research goal was to determine the accessibility and describe the quality of attendance of children at risk of social exclusion in the Croatian ECEC syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The current results are in line with what was observed in other countries. In Croatia [17], the themes that emerged, i.e., 'taking the values of personal and social development in first place' and 'emphasis on every child' seem to be pertinent with the dimension 'child-centred approach' that we reported. In Cyprus [18], the professionals discussed the themes of 'creating learning opportunities for all children' and 'responding to all children's needs by working with and through other adults', which are in line with the dimensions of a 'child-centred approach', 'materials for all children', 'opportunities for communication for all', and an 'inclusive teaching and learning environment'.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The current results are in line with what was observed in other countries. In Croatia [17], the themes that emerged, i.e., 'taking the values of personal and social development in first place' and 'emphasis on every child' seem to be pertinent with the dimension 'child-centred approach' that we reported. In Cyprus [18], the professionals discussed the themes of 'creating learning opportunities for all children' and 'responding to all children's needs by working with and through other adults', which are in line with the dimensions of a 'child-centred approach', 'materials for all children', 'opportunities for communication for all', and an 'inclusive teaching and learning environment'.…”
Section: Discussionmentioning
confidence: 71%
“…Very recently, a few studies have analysed the view of European ECEC practitioners on inclusion, by using content analysis. Bouillet and Domović [17] interviewed 10 Croatian ECEC professionals about their experiences of inclusive education and the risk of social exclusion, and they found two main themes to define inclusion: "the values of personal and social development have taken first place" and the "emphasis on every child, regardless of their chronological age, developmental abilities" (p. 960). Symeonidou and Loizou [18] interviewed seven ECEC teachers in Cyprus and found that the inclusion of children with disabilities pertained to three main elements: creating learning opportunities for all children, refusing the idea that there was just one normal way to learn; rejecting an ableist approach, which brought adults to think that some children were unable to learn; and responding to all children's needs by working with and through other adults.…”
Section: Introductionmentioning
confidence: 99%
“…All participants are female and have a Bachelor's degree in ECEC. Previous analyses carried out as part of the MORENEC project showed that in the ECEC system, when it comes to children in a disadvantaged situation, children living in single-parent families and children with developmental disabilities predominate, while children at risk of poverty and children from ethnic minorities are underrepresented (Bouillet & Antulić-Majcen, 2022).…”
Section: Participantsmentioning
confidence: 99%
“…It has also been found that as the severity of a child's risk of social exclusion increases, accessibility to ECEC decreases (Matković et al, 2020). Poverty and belonging to an ethnic minority (especially among Roma children) are the disadvantaged situations that have the most detrimental effect on children's participation in regular ECEC programmes in Croatia (Bouillet & Antulić Majcen, 2022).…”
Section: A Brief Introduction To the Croatian Ecec Systemmentioning
confidence: 99%
“…This involves the identification of individual characteristics and social circumstances that increase the probability of favorable or unfavorable developmental outcomes. The term “children at RSE” is often equated with concepts such as children in vulnerable situations (Radcliff et al, 2012), disadvantaged children (Schober & Spiess, 2013), marginalized children (Hussain & Warr, 2017), and other related terms that, despite their wide use, are relatively rarely defined and specified (Bouillet & Domović, 2021). The authors agree that the dimensions of RSE are comprehensiveness, multidimensionality, relativity, and dynamic character (Giambona & Vassallo, 2014; Liming & Grube, 2018), but unique and widely accepted classifications and categorizations of RSE in childhood have not been developed (Jopling & Vincent, 2016; Tobia et al, 2017).…”
Section: The Theoretical Framework Of the Studymentioning
confidence: 99%